2011
DOI: 10.1158/1940-6207.capr-10-0333
|View full text |Cite
|
Sign up to set email alerts
|

Enforced Expression of miR-101 Inhibits Prostate Cancer Cell Growth by Modulating the COX-2 Pathway In Vivo

Abstract: It is commonly agreed that there is an association of chronic inflammation with tumorigenesis. COX-2, a key regulator of inflammation-producing prostaglandins, promotes cell proliferation and growth; thus, overexpression of COX-2 is often found in tumor tissues. Therefore, a better understanding of the regulatory mechanism(s) of COX-2 could lead to novel targeted cancer therapies. In this study, we investigated the mechanism of microRNA-101 (miR-101)-regulated COX-2 expression and the therapeutic potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 27 publications
4
79
0
Order By: Relevance
“…To unravel miRNA and its function may provide better understanding of how environmental factors contribute to cancer initiation and development. miR-101-3p has been reported downregulated in many types of cancers, including ESCC (13), prostate (14) and colorectal cancer (15). Through post-transcriptional inhibition of targets, such as cyclooxygenase-2 (COX-2/PTGS2) (16), EZh2/ENX-1 (13), Mcl-1(17), mTOR (18), miR-101-3p could suppress cancer cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To unravel miRNA and its function may provide better understanding of how environmental factors contribute to cancer initiation and development. miR-101-3p has been reported downregulated in many types of cancers, including ESCC (13), prostate (14) and colorectal cancer (15). Through post-transcriptional inhibition of targets, such as cyclooxygenase-2 (COX-2/PTGS2) (16), EZh2/ENX-1 (13), Mcl-1(17), mTOR (18), miR-101-3p could suppress cancer cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…As miR-101 was reported to inhibit COX-2 post-transcriptional expression by binding to the 3'-UTR of COX-2 mRNA in prostate and colon cancer cells (14,15), to verify whether COX-2 is a direct target of miR-101-3p in esophageal cancer cell lines, COX-2 3'-UTR containing the miR-101 binding sites (WT), and binding site mutant (Fig. 3A) were cloned downstream of the luciferase open reading frame to obtain constructs for luciferase activity assay.…”
Section: Mir-101-3p Inhibits Cox-2 Expression By Targeting 3'-utrmentioning
confidence: 99%
“…As an aspect of the relationship with the microRNA-101, the prediction based on PicTar and TargetScan DNA analysis software suggest that COX-2 could be one direct target for miR-101 because miR-101 has a seed region, which is able to bind to the COX-2 mRNA 3-UTR. Such as miR-101 and COX-2 can control the development of mammary gland (Tanaka et al, 2009), colon cancer (Strillacci et al 2009) and prostate cancer (Hao et al, 2011). In recent years, studies have found that some cancer cells ,which have a high-expression of COX-2, their ability of the proliferation and metastasis have also been highly focused.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (9) showed that miR-146a enhances Helicobacter pylori-induced cell apoptosis in human gastric cancer epithelial cells by targeting COX-2. Hao et al (22) demonstrated that enforced expression of miR-101 inhibits prostate cancer cell growth by modulating the COX-2 pathway. miR-16 has also been identified as a potential tumor regulator by targeting COX-2 (23).…”
Section: A B C Dmentioning
confidence: 99%